Reinventing tradition: Russian-Jewish literature between the Soviet underground and post-Soviet deconstruction - Smola, Klavdia (Jews of Russia and Eastern Europe and Their Legacy Series, 2023)
Klavdia Smola explores how the Jewish tradition was reinvented in Russian Jewish literature after a long period of assimilation, the Holocaust and decades of Communism. The process of reinventing the tradition began in the counter-culture of Jewish dissidents, in the midst of the late-Soviet underground of the 1960-1970s, and it continues to the present day.